Social Dynamics: Understanding Conformity, Compliance, and Obedience in Everyday Life - Fikri Alhamdika; Neviyarni S (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Social phenomena such as conformity, obedience, and compliance play an important role in the interaction of individuals in society. Conformity involves changes in one's behavior or beliefs due to group influence, while compliance refers to compliance with the requests of others without internal approval. On the other hand, obedience is obedience to the orders of authority. Factors such as group size, agreement, and legitimacy of authority affect the level of conformity and compliance. Classical research shows that individuals can be influenced to perform actions that are contrary to their moral values. Understanding these dynamics is expected to help individuals recognize social influences on their behavior and develop a critical attitude towards existing norms. The writing of this article uses literature studies to analyze the phenomena of conformity, obedience, and compliance in a social context. The explanations are obtained from various sources, including scientific journals, books, and classic research such as experiments conducted by Solomon Asch and Stanley Milgram.